(3OjhGf GHf NaGLI GdCfOdSjs - (3GHf NaGLI , CHh ESMGb EHQGgje Hf CHj GdaJM Hf NaGLI, CHh ESMGb,J (B533 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPj YR HaVdg, heqf HYO dg, haJb GddSGf HQMeJg, hCfWb GdEfSGf HMceJg, hSOO aCQTO Edi GdESdGe, hYQa HfaSg Hjf GdhMj hGdEdgGe s
(3BNQgG (B:s
(3eHJhQ hBNQ eG ajgG ef bUjOI gGFjI(B: (3aeG HQM GdThb GdeHQM SGejG dCMhi Mhi cqd GdeMGSf eQBg s
(3fSNI KGdKIs
(3hHBNQgG oeWGdaYI ddSjO eMeO Ydj Hf GdSjO oeUWai SfI (B1222(3g```s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B74s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B99 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B765s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs